2011
DOI: 10.1097/grf.0b013e318218c659
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Treatment of Advanced-stage Endometrial Cancer

Abstract: Despite the overall favorable prognosis for women with endometrial cancer, those with advanced and metastatic disease are at significant risk of major morbidity and death. Traditional treatment for advanced-stage endometrial cancer has relied on radiation. The last decade has witnessed a dramatic shift in treatment paradigms for women with advanced-stage endometrial cancer. Chemotherapy is now the cornerstone of treatment for most women with stages III and IV disease. Ongoing trials are exploring multimodal th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The majority of endometrial cancers (72%) are detected and treated at early disease stages (stages I-II), but once it has spread, it is almost impossible to eradicate [3]. Indeed, considerable number of patients with advanced and metastatic (stages III-IV) cancers have a poor prognosis with median survival often <1 year [4]. However, molecular mechanisms explaining the development and metastasis of EC are still unclear.…”
mentioning
confidence: 99%
“…The majority of endometrial cancers (72%) are detected and treated at early disease stages (stages I-II), but once it has spread, it is almost impossible to eradicate [3]. Indeed, considerable number of patients with advanced and metastatic (stages III-IV) cancers have a poor prognosis with median survival often <1 year [4]. However, molecular mechanisms explaining the development and metastasis of EC are still unclear.…”
mentioning
confidence: 99%
“…Hysterectomy and bilateral salpingo-oophorectomy alone or in association with pelvic and para-aortic lymphadenectomy allow a successful treatment in a majority of cases, depending on the stage of the disease. In the event of poor prognostic factors, adjuvant therapies, such as chemotherapy and/or radiotherapy, are associated to surgery [14,15]. Even though some evidence suggests that age is not an independent prognostic factor, older patients seem to present a poorer prognosis.…”
Section: Treatment Of Advanced Ecmentioning
confidence: 98%
“…In this subset of patients, long-term survival is very poor, with 5-year overall survival below 15 %. Moreover, advanced-stage patients for whom chemotherapy or radiotherapy are not possible due to comorbidities present even a poorer prognosis, with a median survival around 12 months [15]. Systemic poly-chemotherapy based on platinum regimes (taxol, adriamycin, cisplatin, or carboplatin), local irradiation, or multi-modal treatment including polychemotherapy and irradiation represents the treatments of choice for advanced EC [9,21].…”
Section: Treatment Of Advanced Ecmentioning
confidence: 99%
“…However, it has been reported that the median survival of women with advanced or recurrent EC on most recent clinical trials is only 1 year [4].…”
Section: Therapy Of Advanced or Recurrent Endometrial Cancermentioning
confidence: 99%
“…The incidence of EC is increasing in the United Kingdom by over 40% since 1993 [1,2]. While the role of adjuvant chemotherapy in patients with early-stage EC is yet to be defined [3], cytotoxic chemotherapy is the mainstay of therapy for metastatic and advanced EC [4].…”
Section: Introductionmentioning
confidence: 99%